Caracterización del Perfil Hematológico y Bioquímico del Lagomorfo Silvestre Ecuatoriano en la Provincia de Cotopaxi - Sánchez Pérez, Carlos Fernando (2019)
The present research work is related to the Hematological and Biochemical Profile of wild Lagomorph in the province of Cotopaxi, the results are interpreted with an analysis of variance with a multiple comparison method and descriptive statistics, for which the INFOSTD program was used ( Dumcan) to categorize the variables, 30 samples were taken from the Páramos, Cotopaxi National Park, the Boliche National Recreation Area, Páramo de Chalupas, Páramo de Cumbijin, Páramo de Salayambo, Páramo de Lamgoa, Páramo de Mulalillo, Páramo de Cusubamba, Ecology Reserve Ilinizas, ranging from 3500 to 4100 meters, were captured with the help of 3 traps with their respective hook (lettuce leaves, cabbage, grass etc.) blood was collected with syringes of 3ml and needles of 23G by 25mm of the marginal vein , placing in minicollect tubes and transporting in a refrigerated cooler to the San Francisco laboratory in the Province of Tungurahua City of Ambato, in terms of Hematology the blood count was found within the normal reference values, the leukogram with respect to variable (leukocyte) decrease (Monocyte) increase and the biochemical profile in the variables glucose, AST, ALT presented an elevation, with respect to Hematology and the chemical profile in relation to sex, does not present a significant difference, the hematology in relation to location does not present any significance, while the chemical profile in relation to the location of the variables Urea, BUN, Creatine, AST, ALT, Total proteins , Phosphorus if they present relevance. Concluding that this research will serve as a source for future research, due to the limited information on these parameters.